HUBUNGAN KELELAHAN KERJA, BEBAN KERJA, DAN LINGKUNGAN KERJA DENGAN KINERJA KARYAWAN - Afridon, Afridon; Ayunda Putri, Kalasta; Oktamianiza, Oktamianiza (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Providing an effective workload and also supported by the provision of adequate work facilities, the agency can find out to what extent its employees can be given a workload so as not to get tired and the extent of its influence on the performance of the agency it self. The purpose of this study was to determine the relationship between work fatigue, workload, and work environment with employee performance at the Public. This research method is quantitative and sampling is 61 people at the Department of Public Works and Spatial Planning Office in Provinci Sumatera Barat. The results show that less than half of the employee's performance is not good (39.3%), 59.0% of tired employees, 60.7% of employees with heavy workloads, and 29.5% of employees stating an unsafe work environment. There is a relationship between work fatigue, workload, work environment and employee performance at the Public Works and Spatial Planning Office. This study concludes that there is a relationship between work fatigue, workload, and work environment on employee performance (p < 0.05). The leadership should provide more adequate facilities, so that employees feel comfortable and safe for activities in the office and K3 safety for outside the office. Keywords: work fatigue, workload, work environment and employee performance